Mechanical and Technical Complication in Patient with Continous Ambulatory Peritoneal Dialysis (CAPD) with Encapsulated Peritoneal Sclerosis - Kandarini, Yenny; Mahadita, Gede Wira; Tedjamartono, Theodore Dharma (Indonesian Journal of Kidney and Hypertension, 2025)
Continuous Ambulatory Peritoneal Dialysis (CAPD) relies on an intraperitoneal catheter for the inflow and outflow of dialysate fluid; therefore, mechanical complications are often encountered. Encapsulated peritoneal sclerosis (EPS) is one of the rare complications in CAPD patients, but it has high mortality and morbidity rates. A case of a patient with EPS was reported in a 53-year-old man in the form of a problem with the dwelling of the CAPD. Patients complain of a longer duration of dwelling with a positive fluid balance. There are no complaints of fever or abdominal pain. Abdominal inspection shows symmetrical, no mass, no wound or pus from the CAPD tip. The patient had a history of recurrent peritonitis. CAPD Cuff was released due to laparoscopy findings with grade IV adhesions in the omentum and peritoneum; it also showed omental cakes and peritoneal fluid with debris. Diagnosis of EPS was established based on the presence of clinical symptoms due to intestinal obstruction and structural disorders due to peritoneal fibrosis, like thickening and adhesions of the intra-abdomen, accompanied by findings of fibrous cocoon or omental cakes in the intestine, with laparotomy and/or laparoscopy. CAPD is related to various complications of infections and non-infections. Although complications related to infections are more often found, non-infection complications such as EPS can also occur in CAPD Patients; therefore, clinicians need to be aware of this complication, especially in patients with a history of recurrent peritonitis.